OG BRYLLUPSREJSEN GIK TIL ET KLOSTER: Ungdomskultur og forbrug blandt koptere i Kairo - Galal, Lise P. (Tidsskriftet Antropologi, 1998)
Lise P. Galal:... and the Honey Moon Trip Went to a Monastery. Youth Culture and Consumption among Copts in Cairo A new cultural outcome of the Coptic orthodox youth who are attempting to integrate their cultural heritage in a modem lifestyle is expressed in the popular trips to the old monasteries of the Egyptian desert. In trying to re-formulate a Coptic identity we see a young couple who prefer the company of their friends from the church instead of their family at such an important occasion as their wedding day. It seems that the church has been successful in fulfilling the modem desires of the young people. The trips to the monasteries resemble this success and satisfy not only a desire for holidays, but also a desire for modem consumption, a style of consumption which in modem times becomes increasingly a sign of cultural identity.